Sjelesorg i farta (Nordic Journal of Practical Theology, 2022)
What is special with pastoral care for youths? That question was given to deacons, youth workers, pastors and others involved in youth ministry in the church of Norway in an online survey (N=314). Their open written answers were qualitatively analyzed. Throughout, they answered that a large part of the pastoral care conversations were not planned, they just happened when the pastoral care worker was doing something else. Second the youth workers emphasized that it was important that they were committed to the youth work over time to let the young people experience that they are available and have time to talk. And third, the material told us that the leaders experienced that young people need adult leaders with the ability to build trust and relationship among youngsters and that they knew what was going on among the youngsters. The pastoral care providers showed reflected understanding of their role, and seemed to draw on both their experience and education, and they thought that they were capable to give support to the young person. This article discusses spontaneous pastoral care for youth in light of former research and the present SOFA project’s interest in the interactions of pastoral care and community building. We hope this can be of influence on how we educate and give leadership training to the young people in the church.